Oleuropein as a bioactive constituent added in milk and yogurt - Zoidou, E.a b; Magiatis, P.b; Melliou, E.b; Constantinou, M.b; Haroutounian, S.c; Skaltsounis, A.-L.b (Food Chemistry, 2014)
Oleuropein is a bioactive natural product from olives known to display a broad variety of health beneficial properties. However its presence in most edible olives is lowered due to debittering. In this respect, we envisaged the incorporation of oleuropein into dairy products (cow’s milk and yogurt) aiming to produce novel functional foods. Additionally, an analytical method for the monitoring of oleuropein in milk and yogurt was also developed and validated. Oleuropein was not affected during heat treatment of milk, while during the milk fermentation process it was not hydrolysed by the produced acids. Oleuropein was not metabolised by lactic acid bacteria, did not inhibit their growth and its stability in the final products was proven. The novel products displayed same taste, colour and texture as the conventional ones. Results herein indicate that oleuropein can be added as an active ingredient in milk and yogurt preparations to provide two novel functional dairy products. © 2014 Published by Elsevier Ltd.
Keywords: Active ingredients; Analytical method; article; Dairy products; Fermentation; Fermentation process; flavor; food color; food texture; functional food; Functional milk; Functional yogurt; heat treatment; high performance liquid chromatography; HPLC; hydrolysis; Lactic acid bacteria; lactic acid bacterium; milk; Oleuropein; olive; oxidation; pH measurement; Taste; thermostability; ultra performance liquid chromatography; yoghurt